Spatiotemporal Correlation of Epileptiform Activity and Gene Expression in vitro - Schlabitz, Sophie; Monni, Laura; Ragot, Alienor; Dipper-Wawra, Matthias; Onken, Julia; Holtkamp, Martin; Fidzinski, Pawel (Frontiers in Molecular Neuroscience, 2021)
Epileptiform activity alters gene expression in the central nervous system, a phenomenon that has been studied extensively in animal models in vivo. Little is known, however, about the situation in human brain tissue. Here, we asked whether an in vitro model of seizures is suitable to investigate changes in gene expression due to epileptiform activity and tested this hypothesis in both rodent and human brain slices. We focused on three genes relevant for seizures and epilepsy: FOS proto-oncogene (c-Fos), inducible cAMP early repressor (Icer) and mammalian target of rapamycin (mTor). Seizure-like events (SLEs) were induced by 4-aminopyridine (4-AP) in rat entorhinal-hippocampal slices and by 4-AP / 8 mM potassium in human temporal lobe slices obtained from surgical treatment of epilepsy. SLEs were monitored simultaneously by extracellular field potentials and intrinsic optical signals (IOS) for 1-4 h, mRNA expression was quantified by real time PCR. In rat slices, both duration of SLE exposure and the SLE onset region were associated with increased expression of c-Fos and Icer while no such association could be shown for mTor expression. Similar to rat slices, c-FOS induction in human tissue was increased in slices with epileptiform activity. Our results indicate that irrespective of limitations imposed by ex vivo conditions, in vitro models represent a suitable tool to investigate gene expression. Future studies applying transcriptome-wide approaches are thus likely to reveal novel candidates involved in the human pathophysiology of epilepsy and possibly other CNS pathologies.